RELASI AKTOR DALAM PENETAPAN KEBIJAKAN KAWASAN KOTA PENDIDIKAN DI KABUPATEN MAJENE - Nurfadilah; Andi Yakub; Sakinah Nadir (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Abstract Actor relations in determining policies for the Education City area in Majene Regency. This study examines actor relations in determining the education city area in Majene Regency involving actors with various interests. Policy determination lies in the central position of the various political actors themselves, that the validity of any public policy determination process cannot be understood thoroughly without understanding the processes that occur, where actors interact with each other. The urgency in this research is related to why Majene is used as an educational city and how the interactions between actors in forming networks include and safeguard their interests. The data collection techniques used in this research were observation, in-depth interviews, and documentation. To obtain the data needed for this research, internet surfing and field research were carried out. The analysis technique used in this research uses the Miles and Haberman model, namely: Data Reduction, Data Display (Data Presentation), and Drawing Conclusions Keywords: Actor relations, policy determination, Education City, Majene Regency.